Konsep Epistemologi Perspektif Al-Kindi: Modifikasi Epistemologi Yunani - Amir Sahidin; Abdurahim Abdurahim (Jurusan Aqidah dan Filsafat Islam Universitas Negri Sunan Gunung Djati Bandung, 2023)
Al-Kindi was the first Arab thinker who paid great attention to epistemology. Although al-Kindi adopted many of the epistemological theories of earlier Greek philosophers, al-Kindi's epistemology has fundamental differences and more values due to his belief in Islamic principles. Based on that, this research will discuss the epistemological concept of al-Kindi's perspective. Through a library research study with a descriptive-analytical approach, it can be concluded, first: al-Kindi's epistemological concept is different from the epistemological concept of the Greek philosophers who negate the role of revelation in it. Second, al-Kindi is very concerned with 'illah or the cause of the nature of a science, which includes material, formal, efficient and final causes, all of which begin and end in the cause of al-haq or God. Third, there are three sources of al-Kindi's knowledge, namely the five senses, rational and divine knowledge which is the highest science.